Review: profil disolusi dan media disolusi yang baik pada tablet rifampicin - Mahaswari, Anak Agung Istri Rani; I Gusti Ngurah Agung Dewantara Putra; Eka Indra Setyawan (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
The development of generic drug consumption in Indonesia is relatively slow. This is because generic drugs are still underestimated by stakeholders for various reasons, the most classic and fundamental is quality. So it is necessary to test the dissolution rate of a drug preparation, so that the dissolution test can be a method to prove the quality of a preparation including generic and branded rifampicin tablets. Objective: To find out how the good dissolution profile onrifampicin tablets branded and with the logo and to find out how good the invivo and in-vitro correlation coefficient values are on the dissolution media. Results: There is no significant difference in DE45 between branded and generic rifampicin tablets, so the results obtained indicate that the brand and generic rifampicin tablets have the same efficacy and quality. Conclusion: The greater the dissolution time, the higher the dissolved rifampicin level. Where the DE45 value indicates the speed of drug dissolution into the medium approaching the in vivo drug absorption profile. The results show that there is no significant difference in DE45 between branded and generic rifampicin tablets, so that the results obtained indicate that the brand and generic rifampicin tablets have the same efficacy and quality. The data show a good correlation with the yield obtained from the dissolution medium containing 0.4% (w/v) sodium lauryl sulfate. Furthermore, the in vitro-in vivo correlation value obtained from the 0.4% (w/v) sodium lauryl sulfate solution medium was in accordance with the in vivo correlation coefficient. Then the 0.4% (w/v) sodium lauryl sulfate solution is a suitable dissolution medium for the fixed dose combination of rifampicin-isoniazid.